2007
DOI: 10.1002/hep.21879
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human liver δ-aminolevulinic acid synthase by bile acids

Abstract: Aminolevulinic acid synthase 1 (ALAS1) is the rate-limiting enzyme of heme synthesis in the liver and is highly regulated to adapt to the metabolic demand of the hepatocyte. In the present study, we describe human hepatic ALAS1 as a new direct target of the bile acidactivated nuclear receptor farnesoid X receptor (FXR). Experiments in primary human hepatocytes and in human liver slices showed that ALAS1 messenger RNA (mRNA) and activity is increased upon exposure to chenodeoxycholic acid (CDCA), the most poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 79 publications
1
25
0
Order By: Relevance
“…4 ). Such a species-dependent regulation has also been observed for other human FXR target genes, including syndecan-1 ( 36 ), fi brinogen ( 37 ), ␣ A-crystallin ( 38 ), peroxisome proliferator-activated receptor ␣ ( 39 ), hepatic lipase ( 40 ), ALAS1 ( 29 ), fetuin-b ( 41 ), and PCSK9 ( 42 ). The reason for such expansion in the repertoire of FXR targets in humans, compared with rodents, remains obscure.…”
Section: Identifi Cation and Functional Characterization Of Putative mentioning
confidence: 86%
See 1 more Smart Citation
“…4 ). Such a species-dependent regulation has also been observed for other human FXR target genes, including syndecan-1 ( 36 ), fi brinogen ( 37 ), ␣ A-crystallin ( 38 ), peroxisome proliferator-activated receptor ␣ ( 39 ), hepatic lipase ( 40 ), ALAS1 ( 29 ), fetuin-b ( 41 ), and PCSK9 ( 42 ). The reason for such expansion in the repertoire of FXR targets in humans, compared with rodents, remains obscure.…”
Section: Identifi Cation and Functional Characterization Of Putative mentioning
confidence: 86%
“…5A , IR1 elements in ADH1A , ADH1B , and ADH1C promoters differ from 2, 3, and 4 nucleotides, respectively, from the consensus FXRE. The presence of a T at position 3 and a C at position 10 of the IR1 element are permissive (e.g., FXREs of FGF19 and ALAS1 , respectively) ( 10,29 ). In contrast, A into G conversion at the sixth position, as it occurs in the ADH1C element, is detrimental to receptor binding ( 27,28 ).…”
Section: Identifi Cation and Functional Characterization Of Putative mentioning
confidence: 99%
“…Other investigators (Fraser et al, 2003;Handschin et al, 2005;Peyer et al, 2007) have shown that several transcription factors including nuclear receptors CAR, PXR, FXR and HNF4α as well as the coactivator PGC-1α mediate the transcriptional regulation of ALAS1 to various stumuli such as fasting, or upon the exposure to endo-and xenobiotics. Since it is recently reported that ALAS1 expression is repressed by heme at a transcriptional level, mediating by recently identified nuclear receptors such as Rev-erbα (Yin et al, 2007;Wu et al, 2009), we tried to identify the site of the enhancer region involved of nuclear receptors in down-regulation of the expression of the mouse ALAS1 transcription, which is exerted by the end product heme.…”
Section: Discussionmentioning
confidence: 99%
“…More likely is the possibility that intracellular heme levels offer a point of access for modification of the characteristics of the circadian rhythm. There are a number of examples of regulatory inputs that modify Alas1 expression including bile acids [24], nutritional status via PGC-1α [25], and xenobiotics [26,27]. Additionally, regulation of heme oxygenase, which controls heme degradation, is another mechanism that may be used to modify the mammalian clock via modulation of intracellular heme levels.…”
Section: Discussionmentioning
confidence: 99%